Circular RNAs in Cardiac Regeneration: Cardiac Cell Proliferation, Differentiation, Survival, and Reprogramming - Mester-Tonczar, Julia; Hašimbegović, Ena; Spannbauer, Andreas; Traxler, Denise; Kastner, Nina; Zlabinger, Katrin; Einzinger, Patrick; Pavo, Noemi; Goliasch, Georg; Gyöngyösi, Mariann (Frontiers in Physiology, 2020)
Circular RNAs (circRNAs) are long non-coding RNAs characterized by a covalently closed loop structure. This closed-loop shape is the result of a backsplicing event in which the 3’ and 5’ splice sites are connected together. Through the lack of 3’ poly(A) tails and 5’ cap structures, circRNAs are more stable than linear RNAs. The increased stability stems from the higher resistance of the circular loop to exonucleases. Additionally, the majority of identified circRNAs are conserved across different species, implying a high evolutionary significance. These molecules have recently been becoming an even greater focus of research due to their wide array of biological functions, ranging from acting as micro RNA (miRNA) sponges to the regulation of protein production, and having a regulatory role in cell differentiation, proliferation and senescence. In the area of cardiovascular disease research in particular, circRNA-related discoveries have opened the door for the development of potential diagnostic and therapeutic tools. In this review we summarize the current state of knowledge regarding circRNAs in cardiac regeneration and their potential role as therapeutic and diagnostic targets in cardiovascular disease.